2017
DOI: 10.4317/medoral.21694
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of peri-implant bone loss between conventional drilling with irrigation versus low-speed drilling without irrigation

Abstract: BackgroundTo compare the technique of high speed drilling with irrigation and low speed drilling without irrigation in order to evaluate the success rate and peri-implant bone loss at 12 months of follow-up.Material and MethodsA randomized, controlled, parallel-group clinical trial was carried out in patients requiring dental implants to rehabilitate their unitary edentulism. Patients were recruited from the Oral Surgery Unit of the University of Valencia (Spain) between September 2014 and August 2015. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 27 publications
(25 reference statements)
3
20
0
Order By: Relevance
“…2 Numerous varied ways to implant site preparation had been analyzed: (a) traditional preparation, which is the continuing expansion of the drilling location by gradual additions of the drill width;(b) simplified preparation, which contains the decrease in the count of drills by usage of a pilot drill followed by a definite drill; (c) biological preparation, which contains low speed preparation without irrigation for gradual location preparation; and (d) single bur preparation, which have been established with unique drills with four-bladed surface and external irrigation. 3 Concerning the drilling speed, some authors have introduced that there was no significant difference in bone healing from the usage of different drilling velocities. As Ribeiro Junior et al (2007) 4 studied the mandibular bone healing defects done in rabbits using three different rotary protocols.…”
Section: Introductionmentioning
confidence: 99%
“…2 Numerous varied ways to implant site preparation had been analyzed: (a) traditional preparation, which is the continuing expansion of the drilling location by gradual additions of the drill width;(b) simplified preparation, which contains the decrease in the count of drills by usage of a pilot drill followed by a definite drill; (c) biological preparation, which contains low speed preparation without irrigation for gradual location preparation; and (d) single bur preparation, which have been established with unique drills with four-bladed surface and external irrigation. 3 Concerning the drilling speed, some authors have introduced that there was no significant difference in bone healing from the usage of different drilling velocities. As Ribeiro Junior et al (2007) 4 studied the mandibular bone healing defects done in rabbits using three different rotary protocols.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid this, most implant systems use irrigation as part of the drilling protocol. However, a randomized clinical trial has suggested that drilling without irrigation could be viable and comparable to drilling with irrigation in terms of bone loss and early implant failure at one year of follow-up [5]. This drilling technique without irrigation allows better visualization of the drilling area and better control of the drill and of bone harvesting.…”
Section: Introductionmentioning
confidence: 99%
“…In a randomized, controlled, parallel-group clinical trial, twenty-five patients were recruited. [ 26 ] Fifteen implants were installed in sites prepared using drills at high-speed drilling with irrigation (group A), while fifteen implants were installed in sites prepared using drills at low speed without irrigation (Group B). After 12 months, the success rate at an implant level was 93.3% in group A and 100% in group B.…”
Section: Introductionmentioning
confidence: 99%